2018
DOI: 10.3390/toxins10050177
|View full text |Cite
|
Sign up to set email alerts
|

Proteopeptidomic, Functional and Immunoreactivity Characterization of Bothrops moojeni Snake Venom: Influence of Snake Gender on Venom Composition

Abstract: Venom composition varies across snakes from all taxonomic levels and is influenced by the snakes’ age, habitat, diet, and sexual dimorphism. The present study reports the first in-depth investigation of venom composition in male and female Bothrops moojeni (B. moojeni) snakes (BmooM and BmooF, respectively) through three proteomics approaches associated with functional, cytotoxic, and immunoreactivity characterization. Compared with BmooM venom, BmooF venom exhibited weaker hyaluronidase, metalloproteinase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 57 publications
3
37
1
Order By: Relevance
“…This was also reflected in the pools: male pool had a higher activity than female pool. Similar results were also observed in other species, like B. jararaca and B. moojeni [34,77]. This result was corroborated by mass spectrometry identification, in which a higher percentage of PLA 2 was found in the male pool.…”
Section: Functional Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…This was also reflected in the pools: male pool had a higher activity than female pool. Similar results were also observed in other species, like B. jararaca and B. moojeni [34,77]. This result was corroborated by mass spectrometry identification, in which a higher percentage of PLA 2 was found in the male pool.…”
Section: Functional Analysissupporting
confidence: 87%
“…However, male venom pool showed higher activity compared to the female pool ( Figure 3C). Although contrasting, the same behavior was observed in B. moojeni [34]. Similar to collagenolytic activity, LAAO activity differed individually.…”
Section: Functional Analysissupporting
confidence: 57%
See 1 more Smart Citation
“…These enzymes are not toxic themselves, but potentiate the effect of ion channel toxins present in venoms, acting as spreading factors [ 69 ]. Hyaluronidases have been identified in many animal venoms, such as those of insects [ 70 ], arachnids [ 8 , 18 , 19 , 71 , 72 ], and snakes [ 73 ]. We found three transcripts that putatively code for hyaluronidases, of which only transcript SgeEnzHya01 was recovered with the complete CDS ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As several studies have shown correlations between different ecological, geographical, genetic and/or developmental factors and the venom proteome, e.g. different diets [30][31][32][33], regional separation of populations [10,[34][35][36], sex [37][38][39] or age [40][41][42][43] it would be ideal to characterize venom composition from a representative cohort of individual animals. However, due to the time consuming nature and expensive costs associated with de-complexing bottom-up venom analysis, most venom compositions reported so far [16], were analyzed from a single pool of venom that was sourced from different numbers of individuals.…”
Section: Introductionmentioning
confidence: 99%